Animation in Social Transformation: Representation of Environmental Destruction and Humanistic Solution for Solar Technology in Scarygirl (2023) - Putri Ayienda Dinanti; Daffa Afif Nabillah (Dinasti International Journal of Education Management And Social Science, 2024)
Animation films can serve as a medium for addressing environmental issues in society. Within this context, this research aims to reveal how human technology exploits nature and renewable energy sources in the animation film Scarygirl. It was directed by Ricard Cussò in 2023, which includes themes addressing environmental issues. Using a qualitative descriptive method, the researcher obtained findings and conducted a deeper analysis of the film. This article employs Lawrence Buell's theory of Ecocriticism to analyze the scenes and dialogues from the film. The research demonstrates that the text and visuals depict intentional environmental destruction and the exploitation of solar energy for personal gain. These representations of environmental issues bring new thoughts and perspectives on humanistic solutions that can be implemented for social transformation.